Charge and temporal characterisation of silicon sensors using a two-photon absorption laser. (1st February 2022) - Geertsema, R.; Akiba, K.; van Beuzekom, M.; Bischoff, T.; Heijhoff, K.; Snoek, H.
Abstract: First measurements are presented from a newly commissioned two-photon absorption (TPA) setup at Nikhef. The characterisation of the various components of the system is discussed. Two planar silicon sensors, one being electron collecting and one hole collecting, are characterised with detailed measurements of the charge collection and time resolution. The TPA spot is determined to have a radius of 0.975(11) μm and length of 23 μm in silicon. The trigger time resolution of the system is shown to be maximally 30.4 ps. For both sensors, uniform charge collection is observed over the pixels, and the pixel side metallisation is imaged directly using the TPA technique. The best time resolution for a single pixel is found to be 600 ps and 560 ps for the electron and hole collecting sensors respectively, and is dominated by ASIC contributions. Further scans at different depths in the sensor and positions within the pixels have been performed and show a uniform response. It is concluded that the TPA setup is a powerful tool to investigate the charge collection and temporal properties of silicon sensors.